Prevalence of subclinical and overt hypothyroidism in infertile women - Pushpagiri, Niroopama; Gracelyn, Leila J.; Nagalingam, Saranya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hypothyroidism has a significant effect on fertility causing anovulatory cycles, luteal phase defect, hyperprolactinemia and sex hormone imbalances. To identify potential and overt hypothyroidism, thyroid screening should be done for all infertile women. The objective of the study was to find the prevalence of subclinical and overt hypothyroidism among infertile women, to find the correlation of hypothyroidism with hormonal and metabolic parameters associated with infertility. Methods: Hospital based analytical cross sectional study was conducted for one and half years among 300 infertile women with primary and secondary infertility. Women with primary and secondary infertility. All hypothyroid women on thyroxine supplementation, male factor infertility, female factor infertility like tubal factor, anomalies of the urogenital tract, obvious organic lesions in the pelvis and women unwilling to participate or sign the informed consent. Results: The prevalence of hypothyroidism in infertile women was 27%. Among them, 25% were subclinical hypothyroid and 2.33% overt hypothyroid. Menstrual dysfunction was observed in 52% of subclinical and 51.15% of overt hypothyroid women, predominant type being oligomenorrhea. We found a negative correlation of hypothyroidism with the family history of thyroid disease. 91.4% of hypothyroid infertile women were obese and the association was strongly significant. Prevalence of hyperprolactinemia in infertile women was 24.67%. The association of hyperprolactinemia with hypothyroidism was 23%. Raised LDL levels were observed in 80% of subclinical and 100% overt hypothyroidism infertile women. Conclusions: Hypothyroidism alters the Hypothalamo-Pituitary ovarian axis and is one of the important etiological factors of female infertility. Most of the women were asymptomatic. Hence every infertile woman should be screened for thyroid profile to open better prospects of conception.